The Application of Random Text Active Learning Strategies to Improve Student Learning Outcomes in Hadith Subjects at Class 1 of KMI Darussalam Modern Gontor Islamic Institution - Nurul Azizah; Agus Budiman; Abu Darda; Lusi Lathifatul Qolbi (At-Ta'dib, 2021)
The success of learning can be seen in terms of processes and results. Data on student learning outcomes at the beginning of the semester founded that only 13% of class 1E students had reached the KKM. One of the important components in the learning process is the learning strategy. The Random Text Active Learning Strategy, because the random text strategy makes students remember the surahs and text of hadits .The Random Text Active Learning Strategy increases the activeness and learning outcomes of grade 1E students on Hadith subject at KMI Darussalam Gontor Islamic Boarding School. The aim of this study are: 1) to increase in a learning activity of class 1E in Hadith material through the Random Text Active Learning Strategy. 2) to the improvement of student learning outcomes 0f class 1E in Hadith material through the Random Text Active Learning Strategy. This research is a Classroom Action Research (CAR) with Kemmis and Mc Taggart model. methods to data collection used tests and observations. The subject of this research is class 1E KMI as 39 students. Classroom action research was carried out in two cycles consisting of planning, implementation, observation, and reflection. The results of this study are: 1) The implementation of Random Text Active Learning Strategy can increase the student's learning activity in the Hadith subject for class 1E at KMI Darussalam Gontor Islamic Boarding School, reached 59% or 34 students in the first cycle and increased by 84% or 39 students. While the increase from the first cycle to the second cycle reached 25%. 2) The Random Text Active Learning Strategy is proven to be effective to increase student learning outcomes, reaching 26 students or 67% in the first cycle and increasing to 34 students or 87% in the second cycle.